Agroekologija s primeri agroekoloških praks - Borec, Andreja (2021)
Agroecology with Examples of Agroecology Practices. The purpose of this book is to illustrate how the basic principles of agroecology work in different agricultural environments and how they can be applied in solving practical cases. The first part of the book is intended for a more theoretical understanding of the development of agro-ecological approaches, presentation of basic principles and various agro-ecological practices at the level of production systems and agricultural landscape. In the second part of the book, we tried to highlight practical examples of agroecological practices of different agricultural environments and disciplines.Although it was not possible to cover all important agroecological aspects in agriculture, we hope that the book will provide a basic insight into the principles, patterns and methodology for integrating agroecology into various agricultural practices and will be a suitable learning tool for students or convenient reading for professionals or other general public.
Keywords: Agriculture; agroecology; sustainability; livestock farming; soil biota; carbon sequestration; biodiversity; organic farming; local market